2015
DOI: 10.1016/j.tvjl.2015.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Agreement between veterinary patient data collected from different sources

Abstract: Determining the accuracy of the electronic medical record (EMR) is vital to the progress of practice-based research. The aim of this study was to determine the agreement between the EMR and other sources of signalment data. Data were gathered during direct observation of small animal consultations in eight veterinary practices. Breed, age, sex and neuter status were recorded, where available, from the EMR, owner and observer and then compared for agreement. Agreement was 'almost perfect' or 'strong' for 18/28 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The study applied a secondary use as a research resource to clinical data from primary-care veterinary practices. Although this offered benefits from reflecting all disorders recorded in the study dogs and that these diagnoses were made to primary care veterinary standards, it is also possible that the results underestimated conditions that were less likely to lead to veterinary presentation or to being formally recorded in the clinical records [ 66 ]. Normalisation of disorders within breed that are de facto an extreme conformation (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The study applied a secondary use as a research resource to clinical data from primary-care veterinary practices. Although this offered benefits from reflecting all disorders recorded in the study dogs and that these diagnoses were made to primary care veterinary standards, it is also possible that the results underestimated conditions that were less likely to lead to veterinary presentation or to being formally recorded in the clinical records [ 66 ]. Normalisation of disorders within breed that are de facto an extreme conformation (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The recording of data within electronic medical records are not always accurate or consistent8 and it was evident when examining the case records that there was variation in clinical record keeping between practitioners. Additionally, there were differences in individual practitioner recording, particularly when there had been multiple cases attended in the same ‘out‐of‐hours’ period.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, research from the human health field has suggested the coding of clinical information is often too simplified to provide a rich and complex representation of both patient and disease needed for research (Jollis et al, 1993). It has been reported that there is often disagreement between the data in coded portions and free-text portions of the human medical record (Stein et al, 2000) and in the veterinary context (Robinson et al, 2015). These examples highlight some of the challenges involved with the use of routinely captured patient data for research (Benchimol et al, 2015).…”
Section: Introductionmentioning
confidence: 99%